2021
DOI: 10.35961/tanjak.v2i1.119
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Skills in Guiding Discussion in Century Learning 21

Abstract: Skills to guide small group discussions conducted by teachers in 21st century learning , using descriptive methods in qualitative research. Descriptive method in research is research for the purpose of explaining or describing events, objects, circumstances, or variables that are explained using numbers and words. Type a descriptive method in research qualitative is a kind of library research ( library research ) literature documents from various sources related to the keter. Visible lead small group discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The existence of group investigation with guided discussion by the teacher for some students was considered more understandable. Of course, teacher skills are needed to guide the discussion to be more effective (Fikri et al, 2021). So, teacher competence is essential, and teachers must master the learning model applied to their students.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of group investigation with guided discussion by the teacher for some students was considered more understandable. Of course, teacher skills are needed to guide the discussion to be more effective (Fikri et al, 2021). So, teacher competence is essential, and teachers must master the learning model applied to their students.…”
Section: Resultsmentioning
confidence: 99%
“…Other research found that the PjBL learning model requires students to develop skills, such as collaborating and reflecting (Isman et al, 2022;Mega Elvianasti et al, 2022). In addition, PjBL helps students to improve social attitudes in respecting the opinions of others, students also become more confident in speaking and expressing opinions in the learning process (Fikri et al, 2021;Mamahit et al, 2020). The PjBL learning model can improve problem-solving skills and encourage students to practice students' communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…Diakhir kegiatan dilakukan diskusi yaitu suatu proses yang dilaksanakan dengan teratur serta melibatkan sekelompok individu dalam sebuah interaksi yang dilakukan secara langsung dengan tujuan untuk saling membagi informasi, memecahkan masalah, dan membuat keputusan (Fikri et al, 2021). Tutor memberikan studi kasus kepada para santri untuk bersama -sama dikerjakan dan diberikan waktu untuk mengulang materi yang sudah diberikan.…”
Section: Penutupunclassified